PERTUMBUHAN DAN HASIL TANAMAN KUBIS KROP (Brassica oleracea L.) DATARAN RENDAH AKIBAT PEMBERIAN DOSIS PUPUK KANDANG AYAM FERMENTASI DAN PUPUK NITROGEN ANORGANIK - Retno Tri Purnamasari; Sulistyawati Sulistyawati; Fajar Hidayanto; Reza Hardiansah (BUANA SAINS, 2022)
The aimed of this study was to obtain the dose of fermented chicken manure and inorganic nitrogen fertilizer for the high growth and yield of cabbage. The study used a Randomized Block Design with one factor, namely the use of a combination of fermented chicken manure and inorganic nitrogen fertilizer. The first treatment was fermented chicken manure 15 tons ha-1 combined with 75% inorganic nitrogen fertilizer; The second treatment was fermented chicken manure 15 tons ha-1 combined with 50% inorganic nitrogen fertilizer; The third treatment was fermented chicken manure 20 tons ha-1 combined with 75% inorganic nitrogen fertilizer; The fourth treatment was fermented chicken manure 20 tons ha-1 combined with 50% inorganic nitrogen fertilizer; The fifth treatment was fermented chicken manure 25 tons ha-1 combined with 75% inorganic nitrogen fertilizer; The sixth treatment was fermented chicken manure 25 tons ha-1 combined with 50% inorganic nitrogen fertilizer. The results showed the effect of the dose of fermented chicken manure and inorganic nitrogen fertilizer on the growth and yield of cabbage crop, the application of fermented chicken manure 25 tons ha -1 combined with inorganic nitrogen fertilizer as much as 75% produces the highest yield on all observation parameters with the highest crop weight weighing 27.37 tons ha-1.